Inovação em gestão e em formatos organizacionais: um estudo em organizações brasileiras e portuguesas - Daniel Paulino Teixeira Lopes (2009)
The main objective of this dissertation was to identify and to analyze how innovation in management and in organizational forms happens in Brazilian and Portuguese organizations, considering the innovation systems in which these organizations are inserted. In order toachieve this objective, it was necessary to build up a literature review that did not restrict the research object into one specific discipline, but that at the same time would allow the choice of an appropriate methodology for the study of this type of innovation. The theoretical discussion covered general concepts regarding innovation, interrelation betweencompetitiveness, innovation systems, theories of the firm and organizational theories, as well as the issues related to Brazilian and Portuguese contexts that permitted the understanding and the investigation of the phenomenon of innovation in management and in organizational forms. The methodology was defined around an empirical research carried out through secondary data analysis from official innovation surveys, and through two exploratory case studies. The secondary data analysis intended to get an overview of the phenomenon,according to the available data from PINTEC 2005, in the case of Brazil, and CIS 4, in the case of Portugal. The exploratory case studies, in turn, deepened the analysis in two high performance organizations from the telecommunications sector, industry which presented high rates of innovation in management and in organizational forms in both countries. Data from the Brazilian Oi and the Portuguese PT Inovação have been analyzed following procedures of qualitative research. The findings indicate the connection between innovations in management and in organizational forms and innovations in products and processes, theconceptual diversity related to the type of innovation investigated, the similarities and differences in the results of the researches from Brazil and Portugal, and the diffusion of innovations, reported in both case studies.